Study of phase transition in (Pb,Ba)TiO(3) thin films - Pontes, Fenelon Martinho Lima [UNESP]; Santos, L. S. [UNESP]; Pontes, D. S. L. [UNESP]; Longo, Elson [UNESP]; Neto, S. Claro; Leite, E. R.; Chiquito, A. J.; Pizani, P. S. (American Institute of Physics (AIP), 2008)
Dielectric and Raman scattering experiments were performed on polycrystalline Pb(1-x)Ba(x)TiO(3) thin films (x=0.40 and 0.60) as a function of temperature. The dielectric study on single phase compositions revealed that a diffuse-type phase transition occurred upon transformation of the cubic paraelectric to the tetragonal ferroelectric phase in all thin films, which showed a broadening of the dielectric peak. Diffusivity was found to increase with increasing barium contents in the composition range under study. In addition, the temperature dependence of Raman scattering spectra was investigated through the ferroelectric phase transition. The temperature dependence of the phonon frequencies was used to characterize the phase transitions. Raman modes persisted above the tetragonal to cubic phase transition temperature, although all optical modes should be Raman inactive. The origin of these modes was interpreted as a breakdown of the local cubic symmetry by chemical disorder. The lack of a well-defined transition temperature and the presence of broadbands in some temperature intervals above the paraferroelectric phase transition temperature suggest a diffuse-type phase transition. (C) 2008 American Institute of Physics.